Respiratory management of the infant with type 1 spinal muscular atrophy. Issue 7 (21st June 2005) - Bush, A; Fraser, J; Jardine, E; Paton, J; Simonds, A; Wallis, C
Abstract : A recent paper has highlighted the differences in the respiratory management offered to infants with type 1 spinal muscular atrophy (SMA-1).1 Current views appear polarised between those who would offer nothing, to those who would proceed as far even as tracheostomy and long term invasive ventilation for these infants. Here we offer a personal view, as a possible template for managing a vexed and emotional problem. The complex non-respiratory aspects of the holistic care of these infants will not be discussed.